PYROSEQUENCING AND FUNCTIONAL ANNOTATION ANALYSIS OF MICROBIAL COMMUNITY IN FRESH WATER LAKE IN SAUDI ARABIA - SAMY SELIM; NASHWA HAGAGY (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Metagenomics is providing conspicuous advantage to explore world of unculturable microorganisms in the natural samples to enhance our information about bacterial diversity. Here, we have performed metagenomic analysis of fresh water lake with focus on bacterial community using 454 pyrosequencing techniques. Roche GS FLX software indicated total of 156.253 reads; 15.226 contigs having > 100 bp sequence length whereas 10.481 contigs with > 500 bp sequence length. We have analyzed the bacterial community composition using BLASTN/BLASTX against NT/NR databases with E-value cutoff of 10-5. We have observed a wide array of bacteria from phylum proteobacteria and family Enterobacteriaceae as well as very few viruses from Podoviridae, Siphoviridae and unclassified phages. Moreover, a functional analysis of all 5974 contigs using Rapid Annotation by Subsystem Technology (RAST) was performed and detected 15.319 coding sequences and 197 RNAs in 619 subsystems. The great diversity of microflora present in the lake may reflect the human activity in the area.